Exposure of magnesium oxide boards to various conditions for extended durations. (4th October 2021) - Aiken, Timothy A.; McPolin, Daniel; Russell, Mark; Nanukuttan, Sreejith; Bagnall, Leo
Highlights: Crying behaviour largely attributed to the breakdown and leaching of excess MgCl2 . Investigated RH and temperature values do not affect the stability of certain MgO boards. Mechanical properties were not affected by long term exposure conditions. Certain MgO boards anticipated to remain stable for at least 33 years in average UK climate. Abstract: Evolving construction methods and an increased demand for materials with enhanced fire resistance have created a demand for novel materials within the construction industry. In recent years, MgO boards have become more widely used as a solution to the needs of modern construction. This paper explores the behaviour of magnesium oxide boards during exposure to various temperatures and high levels of moisture. More than 1000 samples were prepared for analysis and the laboratory test durations extended beyond 2 years. Findings indicate that magnesium chloride hydroxide hydrate phases within well proportioned magnesium oxide boards remained stable after exposure to various conditions. Additionally, the mechanical properties were relatively unaffected by exposure to high levels of moisture for extended durations. Findings also indicate that magnesium oxide boards based on magnesium oxysulphate cement are not susceptible to the 'crying' phenomenon. By correlating laboratory performance of magnesium oxide boards with weather data it was possible to ascertain that well proportioned boards would remain stable for at least 33 years in-service in the average UK location.